2021
DOI: 10.1016/j.copsyc.2020.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of religiousness and their connection to racial, ethnic, and atheist prejudices

Abstract: In this article we review the most recent empirical research about the psychology of religion and intergroup prejudices based on race/ethnicity or religious identification. We highlight how social identity fusion, intergroup emotions, perceived value-conflict and threat, and system-justification contribute to degrees of prejudice. We also review connections between religiosity and attitudes toward specific cultural groups (e.g., immigrants, atheists, and religious minority groups). Finally, we conclude with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 66 publications
2
22
0
3
Order By: Relevance
“…Crawford (2017) showed that physical threat was stronger among conservatives. We suggest that persons who continued to believe that reception of Holy Communion in the mouth during the pandemic was still proper may experience a specific form of anxiety, namely higher value threat (see Rowatt and Al-Kire 2021). Previous meta-analytic studies showed that higher value threat is related to prejudices (Riek et al 2006).…”
Section: Discussionmentioning
confidence: 86%
“…Crawford (2017) showed that physical threat was stronger among conservatives. We suggest that persons who continued to believe that reception of Holy Communion in the mouth during the pandemic was still proper may experience a specific form of anxiety, namely higher value threat (see Rowatt and Al-Kire 2021). Previous meta-analytic studies showed that higher value threat is related to prejudices (Riek et al 2006).…”
Section: Discussionmentioning
confidence: 86%
“…Certain dimensions of religiosity is associated with closed-mindedness and prejudice toward a variety of groups, including different races and sexual minorities (Johnson et al, 2012;Rowatt & Al-Kire, 2021), implying unwillingness to accept dissimilar others. Indeed, religiosity is often associated with closed-mindedness and animosity toward a variety of different groups (Rowatt & Al-Kire, 2021), most notably gays and lesbians (Johnson et al, 2012). In contrast, atheists tend to score higher on the Actively Open-Minded Thinking Scale than religious individuals (Pennycook et al, 2014), suggesting that they are relatively more willing to objectively evaluate arguments and perhaps consider diverse, opposing opinions.…”
Section: Is There Anything Good About Atheists?mentioning
confidence: 99%
“…Another potential positive stereotype about atheists is open-mindedness-a willingness to accept people different from them and to consider opposing opinions. 1 Certain dimensions of religiosity are associated with closed-mindedness and prejudice toward a variety of groups, including different races and sexual minorities (Johnson et al, 2012;Rowatt & Al-Kire, 2021), implying unwillingness to accept dissimilar others. Indeed, religiosity is often associated with closed-mindedness and animosity toward a variety of different groups (Rowatt & Al-Kire, 2021), most notably gays and lesbians (Johnson et al, 2012).…”
Section: Positive Stereotypes About Atheists (And Negative Stereotypes About the Religious)mentioning
confidence: 99%
“…Secara stereotip, religiusitas diartikan sebagai pemahaman atas pengetahuan dan keyakinan agama, selain pengaruhnya yang terkait dengan keterikatan emosional atau perasaannya tentang agama. Selanjutnya, perilaku keberagamaan diekspresikan, seperti keanggotaan dan kehadiran dalam kegiatan ibadah, membaca kitab suci, dan berdoa (Hichy et al, 2020;Rowatt & Al-Kire, 2021;Xia et al, 2021). Kecenderungan terhadap keyakinan agama menunjukkan religiusitas seseorang terhadap seperangkat prinsip yang memberikan beberapa kendali sosial bagi individu yang bersangkutan (Jiménez et al, 2019).…”
Section: Kajian Pustakaunclassified